Analysis of Potassium Bromate Contents of Commonly Consumed Loaves of Bread Samples in Tokra-Libya - Rahil, Salwa; El sharaa, Intisar (Journal of Pure & Applied Sciences, 2023)
Bread is one of the most popular foods consumed worldwide. It is a very popular foodstuff consumed in almost every house in Libya as well as in Tokra city as breakfast.  Potassium bromate is an oxidizing agent that has been used as bread additive added to preserve the flavour and teste of the bread but continuing to consume it endangers health as a result of its carcinogenic effect, as it remains in the loaf of bread without disintegration, For this reason, Potassium bromate is banned in several countries, including Brazil, Canada, the European Union and the United Kingdom and the FDA has since 1991 merely encouraged bakers to voluntarily stop using it, with somewhat limited success. In this study, levels of residual bromate were determined in 21commercial breads and traditional loaf types from 7 automated bakeries, except for one, a manual bakery randomly were collected from different local bakeries in Tokra city and its environs (Libya), in Feb. 2023. The tested samples of bread were analyzed using two mothed (qualitative and quantitative analyses) a spectrophotometric method of bromate analysis. Bromate concentrations ranged from 0.07-0.29 μgg-1, with an overall mean concentration of 0.14±0.07 μgg-1(ppm). Significant differences were noticed.